2003
DOI: 10.1038/sj.mp.4001464
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of CRF1 or V1b receptors reverses stress-induced suppression of neurogenesis in a mouse model of depression

Abstract: Repeated exposure to stress is known to induce structural remodelling and reduction of neurogenesis in the dentate gyrus. Corticotrophin-releasing factor (CRF) and vasopressin (AVP) are key regulators of the stress response via activation of CRF 1 and V 1b receptors, respectively. The blockade of these receptors has been proposed as an innovative approach for the treatment of affective disorders. The present study aimed at determining whether the CRF 1 receptor antagonist SSR125543A, the V 1b receptor antagoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
116
1
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 275 publications
(130 citation statements)
references
References 49 publications
12
116
1
1
Order By: Relevance
“…An exciting area of research has been the use of CRH receptor antagonists as antidepressants. Administration of CRH-R1 antagonist reduces chronic stress [108] and induces neurogenesis [93] in a manner similar to that of the antidepressant fluoxetine suggesting that CRH-R1 antagonists have the potential to become a novel class of antidepressants.…”
Section: Future Researchmentioning
confidence: 98%
See 2 more Smart Citations
“…An exciting area of research has been the use of CRH receptor antagonists as antidepressants. Administration of CRH-R1 antagonist reduces chronic stress [108] and induces neurogenesis [93] in a manner similar to that of the antidepressant fluoxetine suggesting that CRH-R1 antagonists have the potential to become a novel class of antidepressants.…”
Section: Future Researchmentioning
confidence: 98%
“…SSRIs or NRIs increase serotonin and/or NE levels, allowing these neurotransmitters to stimulate the cAMP cascade or the Ca 2+ cascade, leading to an increase in CREB and BDNF [92]. Studies indicate that the CRH receptor antagonist reverses the decrease in neurogenesis observed in stressed mice [93]. This suggests the involvement of multiple receptor systems and signal transduction cascades in neurogenesis.…”
Section: Neurotransmitter Systems In Neurogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…V1bR KO mice have also been reported to exhibit markedly reduced aggressive behavior (Wersinger et al, 2002). Moreover, it has been reported that a selective V1bR antagonist produced anxiolytic-and antidepressantlike effects in rodents Serradeil-Le Gal et al, 2002) and reversed stress-induced suppression of neurogenesis in a mouse model of depression (Alonso et al, 2004). V1bR is widely distributed in the central nervous system including the cerebral cortex, hippocampus, and hypothalamus (Lolait et al, 1995;Vaccari et al, 1998), suggesting that V1bR regulates the HPA system and plays a potential role in stress-related behavior.…”
Section: Introductionmentioning
confidence: 98%
“…Furthermore, studies have demonstrated that chronic treatment with antidepressants reverses stress-induced inhibition of neurogenesis in the hippocampal formation (van der Hart et al, 2002;Malberg and Duman, 2003;Alonso et al, 2004;Fuchs et al, 2004;Czeh et al, 2001).…”
Section: Introductionmentioning
confidence: 99%